2022
DOI: 10.3390/biomedicines11010074
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Decreases Intestinal Inflammation in the Ovariectomized Murine Model of Postmenopause

Abstract: Cannabidiol (CBD) (25 mg/kg peroral) treatment was shown to improve metabolic outcomes in ovariectomized (OVX) mice deficient in 17β-estradiol (E2). Herein, CBD effects on intestinal and hepatic bile acids (BAs) and inflammation were investigated. Following RNA sequencing of colon tissues from vehicle (VEH)- or CBD-treated sham surgery (SS) or OVX mice (n = 4 per group), differentially expressed genes (DEGs) were sorted in ShinyGO. Inflammatory response and bile secretion pathways were further analyzed. Colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Both Doeve et al and Vinci et al concluded similarly, reporting little to no impact of cannabinoids on remission or inflammatory biomarkers 29,30 . In contrast, recent studies in animal models of intestinal inflammation have shown a reduction in colonic inflammation, with degrading enzymes for endocannabinoids; such as fatty acid amide hydrolase inhibitors and cannabidiol 37,38 . Another recent study by Moniruzzaman et al reported that the efficacy of cannabidiol could be increased by using protein nanoparticles to treat inflammatory bowel disease 39 .…”
Section: Discussionmentioning
confidence: 85%
“…Both Doeve et al and Vinci et al concluded similarly, reporting little to no impact of cannabinoids on remission or inflammatory biomarkers 29,30 . In contrast, recent studies in animal models of intestinal inflammation have shown a reduction in colonic inflammation, with degrading enzymes for endocannabinoids; such as fatty acid amide hydrolase inhibitors and cannabidiol 37,38 . Another recent study by Moniruzzaman et al reported that the efficacy of cannabidiol could be increased by using protein nanoparticles to treat inflammatory bowel disease 39 .…”
Section: Discussionmentioning
confidence: 85%
“…Bacalia et al examined the impact of CBD on intestinal inflammation, and they found that in female mice, CBD suppresses inflammation in the absence of estradiol, but it enhances inflammation in animals with estradiol [ 10 ]. Yekhtin and colleagues found that both THC and CBD reduced nitric oxide production by lipopolysaccharide (LPS)-stimulated peritoneal macrophages [ 11 ].…”
Section: Original Research Articlesmentioning
confidence: 99%